Durabilitas beton yang mengandung agregat ringan buatan berbahan dasar abu terbang (fly ash) - Ditya Hafiz Rosyidi; Mohammad Sulton; Puput Risdanareni (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2024)
The low fly ash consumption in Indonesia needs to be tackled in order to avoid the pilling of this material. Employing this material as a raw material to produce lightweight aggregate becomes an alternative solution to increase the fly ash consumption, as the aggregate has high portion in the concrete mixture. However, as lightweight aggregate has high porosity, its durability especially in term of water uptake in aggressive environment need to be investigated. Thus, this research aims to observe the durability of concrete containing fly ash-based lightweight aggregate (FA LWA) in salt environment. The Salt environment was mimicked with Sodium chloride and sodium sulfate solution. The FA and EC LWA were used as coarse aggregate replacement with replacement rate 50 and 100% by volume. The physical, mechanical and durability properties of concrete were assessed by conducting the bulk density, compressive strength test and capillary water absorption rate in salt environment. The result shows that the bulk density is inversely proportional to the percentage of LWA content used. In addition, from the concrete capillary water absorption test showed that concrete containing FA LWA obtained a higher absorption value than control concrete. Based on the results of the capillary absorption test using different solutions, it showed that FA LWA concrete was more resistant in an alkaline environment or containing salt solution (NaCl). The results of this study contribute to a new breakthrough that fly ash consumption can be improved by transforming fly ash into artificial lightweight aggregate that has high resistance in marine environment.